2004
DOI: 10.1111/j.1469-0691.2004.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the MexXY efflux pump in amikacin-resistant isolates of Pseudomonas aeruginosa

Abstract: The MexZ-MexX-MexY multidrug efflux system in Pseudomonas aeruginosa was studied to determine its contribution to aminoglycoside resistance. Amikacin-resistant (AR) mutants were generated from P. aeruginosa strain PAO1, and clinical isolates of P. aeruginosa were collected from cystic fibrosis patients. The regulatory gene mexZ and the intergenic region (mexOZ) between mexZ and mexX were investigated for mutation by PCR and DNA sequence analysis. The results showed that 14 of 15 AR clinical isolates and one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 39 publications
5
63
1
Order By: Relevance
“…These results were fully consistent with previously published data showing the absence of horizontally acquired aminoglycoside-modifying enzymes in most CF isolates of P. aeruginosa (29,45,70,83). As the efflux system MexXY-OprM is known to play a major role in emergence of aminoglycoside resistance in CF strains (31,83,84), we assessed its expression at the gene (mexY) and the protein (MexY) levels by reverse transcription RT-PCR and Western blotting, respectively. As expected, all the Tic hs strains were found to overexpress both the mexY gene (11.4-to 58.8-fold) (data not shown) and the MexY protein compared with aminoglycoside-susceptible strains PAO1, 615S, and 3020S (Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…These results were fully consistent with previously published data showing the absence of horizontally acquired aminoglycoside-modifying enzymes in most CF isolates of P. aeruginosa (29,45,70,83). As the efflux system MexXY-OprM is known to play a major role in emergence of aminoglycoside resistance in CF strains (31,83,84), we assessed its expression at the gene (mexY) and the protein (MexY) levels by reverse transcription RT-PCR and Western blotting, respectively. As expected, all the Tic hs strains were found to overexpress both the mexY gene (11.4-to 58.8-fold) (data not shown) and the MexY protein compared with aminoglycoside-susceptible strains PAO1, 615S, and 3020S (Fig.…”
Section: Resultssupporting
confidence: 79%
“…Interestingly, studies in the 1990s demonstrated that the nalB gene encodes a negative regulator of MexAB-OprM (63), a polyspecific efflux system which contributes to the natural resistance of P. aeruginosa toward a wide range of antibiotics including ␤-lactams, tetracyclines, trimethoprim, fluoroquinolones, and novobiocin (36,40). In parallel, another efflux pump, MexXY, which is encoded by a distinct operon (mexXY) on the bacterial chromosome, was found to provide CF isolates with moderate resistance to amino-glycosides, fluoroquinolones, and the zwitterionic cephalosporin cefepime when stably overproduced upon various mutations (31,50,83,84).…”
mentioning
confidence: 99%
“…These data suggest a contribution by efflux pumps through their upregulation and/or permeability alterations in these strains. Antimicrobial compounds, including amikacin, ampicillin, cephalosporins, cefoxitin, chloramphenicol, ciprofloxacin, kanamycin, nalidixic acid, piperacillin, and tetracycline, which demonstrated a reduced effect on one or more of the biocide-tolerant Salmonella strains, are known efflux pump substrates (11,15,27,29,32) of the resistance nodulation and cell division (RND) family (32). In some instances, changes in antibiotic susceptibility profiles were sufficiently large that these could be defined according to CLSI guidelines, whereas others were more modest.…”
Section: Discussionmentioning
confidence: 99%
“…MexZ binds as a homodimer to an inverted repeat region, located in the mexZ-mexX intergenic region, which encompasses the putative mexXY promoter (154). Mutations in mexZ or the mexZ-mexX intergenic region have been associated with hyperexpression of mexXY (85,263). However, overexpression of mexXY has also been detected in mutants not harboring mutations within mexZ or the mexZ-mexX intergenic region (137,240,269).…”
Section: Mexxy Efflux Pumpmentioning
confidence: 99%